2013
DOI: 10.1371/journal.pone.0068531
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome/Degradome-Wide Identification of R. glutinosa miRNAs and Their Targets: The Role of miRNA Activity in the Replanting Disease

Abstract: Rehmannia glutinosa, a traditional Chinese medicine herb, is unable to grow normally in a soil where the same species has recently been cultivated. The biological basis of this so called “replanting disease” is unknown, but it may involve the action of microRNAs (miRNAs), which are known to be important regulators of plant growth and development. High throughput Solexa/Illumina sequencing was used to generate a transcript library of the R. glutinosa transcriptome and degradome in order to identify possible miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Here, a non-redundant R. glutinosa transcriptome contained 87,665 transcripts from two sets of roots and leaves have constructed in our previous study (Li et al, 2013). Approximately 1.97% transcript sequences were found to carry at least one SSR locus (≥18 bp), similar to the 2.8% prevalence in barley (Fraser et al, 2004), 3.2% in wheat (Parida et al, 2006), 3.83% in Ramie (Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Here, a non-redundant R. glutinosa transcriptome contained 87,665 transcripts from two sets of roots and leaves have constructed in our previous study (Li et al, 2013). Approximately 1.97% transcript sequences were found to carry at least one SSR locus (≥18 bp), similar to the 2.8% prevalence in barley (Fraser et al, 2004), 3.2% in wheat (Parida et al, 2006), 3.83% in Ramie (Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 86%
“…In this study, a high-capacity R. glutinosa transcriptome derived from different organs using highthroughput sequencing technology (Li et al, 2013) was built to provide basic support for the development. Meanwhile, Polymorphism level of novel R. glutinosa EST-SSR markers was finely identified based on same R. glutinosa species from different ecological regions.…”
Section: Introductionmentioning
confidence: 99%
“…While some hundreds of miRNA sequences have been identified in Arabidopsis thaliana and rice (Reinhart et al, 2002;Gielen et al, 2016), only 37 R. glutinosa ones have been lodged in the database so far Li et al, 2013). In the study, the application of NGS has identified 18 novel miRNA families of R. glutinosa roots, which enriched the species' sRNA information.…”
Section: Discussionmentioning
confidence: 99%
“…In the study, the application of NGS has identified 18 novel miRNA families of R. glutinosa roots, which enriched the species' sRNA information. An earlier comparison of miRNAs and their mRNA targets between plants growing in fresh soil and second-year plants suggested that miRNAs were likely involved in replanting disease Li et al, 2013). Here, the survey has been extended to plants grown for a third and fourth year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation